Maternal protein deficiency alters primary cilia length in renal tubular and impairs kidney development in fetal rat - Wang, Jun; Zhou, Pei; Zhu, Liangliang; Guan, Hongbo; Gou, Jian; Liu, Xiaomei (Frontiers in Nutrition, 2023)
Introduction Intrauterine malnutrition impairs embryo kidney development and leads to kidney disease and hypertension in adulthood, yet the underlying mechanism remains unclear. Methods With a maternal protein restriction (MPR) rat model, we investigated the critical ciliogenesis factors and β-catenin pathway in FGR fetal kidneys and analyzed the impact of aberrant primary cilia on renal tubular epithelium. Results The data showed decreased nephron number and renal tubular dysgenesis in FGR fetus. FGR fetus showed deregulated expression of ciliogenesis factors including upregulation of IFT88 and downregulation of DYNLT1, accompanied with cilia elongation in renal tubular epithelial cells. Wnt7b, the key ligand for Wnt/β-catenin signaling, was downregulated and nuclear translocation of β-catenin was decreased. The proapoptotic protein was upregulated. In vitro study with HK-2 cells showed that overexpression of IFT88 lengthened the cilia, inhibited β-catenin signaling. Besides, IFT88 overexpression suppressed cell proliferation, activated autophagy, and induced cell apoptosis. Inhibition of autophagy partly restored the cilia length and cell viability. Likewise, knockdown of DYNLT1 led to cilia elongation, suppressed cell proliferation, and promoted apoptosis in HK-2 cell. However, the cilia elongation induced by DYNLT1 knockdown was not autophagy-dependent, but associated with reactive oxygen species (ROS) accumulation. Discussion We elucidated that intrauterine protein malnutrition led to deregulation of ciliogenesis factors and cilia elongation in renal tubular epithelial, inhibited β-catenin signaling, and induced cell apoptosis and ultimately, compromised kidney development.